Study of Types of Speech and Its Specific Characteristics in The English and Uzbeki Languages - Pazilova Nasibaxon Muhammadqosimovna; Qodirova Mashrabhon Kozimjonovna (Zien Journals, 2023)
This article discusses the types of speech in English and Uzbek, the forms of oral and written speech, and the research of communicative qualities of speech in the compared languages.
Keywords: speech; communicative qualities; culture